Effects of Salt, Polyethylene Glycol, and Water Content on Dough Rheology for Two Red Spring Wheat Varieties. Issue 3 (9th January 2017) - Yovchev, Aleksandar G.; Stone, Andrea K.; Hucl, Pierre; Scanlon, Martin G.; Nickerson, Michael T.
Abstract : In this research, the relationship between dough rheology and water behavior was investigated in response to two osmotic regulators, salt (NaCl) and polyethylene glycol (PEG), using two Canadian Western Red Spring (CWRS) wheat varieties (Harvest and Pembina). The effects of NaCl (0.5, 1.0, and 1.5 g/100 g of flour) and PEG 400 (2.5, 5.0, and 7.5 g/100 g of flour) on dough rheology (oscillatory and creep) were estimated by using a central composite design. Variation of NaCl showed a significant effect on the phase angle δ, indicating that increasing the NaCl resulted in a more elastic dough. The opposite trend was observed with the addition of PEG. PEG 400 exerted a softening effect owing to plasticization, so that a more compliant liquid‐like dough was produced. The effects of water content (±10% of farinograph absorption) and PEG molar mass on dough rheology and freezable water content were estimated by using a full factorial design. PEGs with different molar mass (400, ≈1, 600, and 3, 350 g/mol) were added at a concentration of 1 g/100 g of flour. The water content significantly affected all dough rheological attributes, whereas PEG molar mass had no effect. The complex shear modulus ( G* ) decreased with increasing water content, and dough creep compliance ( J max ) increased. The elastic response of dough, determined as the relative elastic part ( J el ) decreased with increasing water content. A high correlation was found between the freezable water content and dough rheological attributes.